Economics today - Miller, Roger LeRoy (New York : Harper & Row, 1985)
The Foundations of Economics by Bade/Parkin, fifth edition shines with a well-targeted content adjustment making it one of the most relevant and up-to-date Principles of Economics texts on the market today. In-text examples, dynamic chapter openers, and applications contain compelling content and real-world issues.
Includes index
Includes bibliographies and indexes.
II 15/01/2019
Loans
Keywords: Economics